5 - L'émergence de l'humanisme dans la représentation littéraire de l'exclusion: by Banda Fall - Banda Fall, (Africa Development, 1998)
Because their patients are doomed to seclusion and rejection, such diseases as tuberculosis, leprosy, plague, madness and AIDS could be experienced as exile or exclusion of some sorts. As for leprosy, it has been associated in quite a few civilisations with the idea of a curse. It is presented as a disease of mythical or even mystical origin. Therefore lepers remain exiles within the realm of their illness; excluded with no other society than their own; experiencing in their environment but contempt and suspicion. In an attempt to deliver patients from the social excommunication they suffer, writers such as the anonymous author of Roman de Tristan et Iseut or Victor Hugo in Fin de Satan, Ibrahim Ly in Toiles d'araignées tried to demystify clichés and to eradicate negative images attached to leprosy.